ANALISIS BED TURN OVER DI RUANG MINA RUMAH SAKIT HARAPAN DAN DOA KOTA BENGKULU - Nofri Heltiani; Iin Desmiany Duri; Endah Dwi Lestari (Jurnal Informasi Kesehatan Indonesia (JIKI), 2021)
Bed Turn Over (BTO) is the average number of patients who use each bed in a certain period. The ideal BTO value is 40-50 times/year. Inpatient indicators related to BTO are very important to pay attention to in efforts to improve service quality. The high BTO has the potential to disrupt the balance of clinical aspects such as hospital nosocomial infections. Based on the initial survey, the BTO value for the last three years at the Bengkulu City Hope and Prayer Hospital has increased, namely in 2016 (58.23 times/year), 2017 (64-65 times year) and 2018 (65 times/year) . This shows that the change of patient beds is very fast so that the use of the bed exceeds the provisions, namely 40-50 times/year, meaning that 1 bed is used by more than 50 patients a year which can cause nosocomial infections. The purpose of this study was to determine the value of BTO in the Mina Room of Harapan Hospital and Prayer in Bengkulu City for the 2019 period. The type of research used in this study was quantitative descriptive with a cross sectional approach. The population and sample were 2,060 inpatients in the Mina Room for the period 2019 with the sampling technique being the total population. The data used is secondary data which is processed by collecting, editing, classification and tabulating and analyzed using the BTO formula. The results of data analysis, the number of patients treated in the 2019 period in the Mina Room were 2,060 patients, with length of care (LD) of 7,435 days/year and an average of 3-4 days/year and the number of patients discharged (living or dead) in the Mina Room. 2,045 patients came out alive and 15 patients died, so that the BTO value in the Mina Room reached 93.58 times/year. The high BTO value in the Mina Room in the 2019 period resulted in a fairly high nosocomial infection of 12%. It is hoped that the hospital will add more beds in the Mina Room to prevent or reduce the occurrence of nosocomial infections.